AKTIVITAS IMUNOMODULATOR EKSTRAK ETANOL DAUN JAMBU BIJI (Psidium guajava L.) - Irene Puspa Dewi Dewi; Verawaty; Tuty Taslim (JURNAL KATALISATOR, 2022)
This study was aimed to assess immunomodulatory activity of guava leaf (Psidium guajava L.) ethanol extract. Guava leaves contain flavonoid compounds that can be used as immunomodulators. The parameters to be determined were the percentage of phagocytosis and the phagocytic capacity of mouse macrophage cells. A total of 25 mice were divided into 5 groups, namely a negative control, a positive control, a dose100 mg/Kg BW, a dose of 500 mg/Kg BW, and a comparison group. The mice were treated according to their respective groups for 7 days and on the 8th day the mice were injected intraperitoneally with Staphylococcus aureus (SA) bacteria suspension, except for the negative control group. After 1 hour, mice in all groups were sacrificed and their peritoneal fluid were taken to calculate the percentage of activity and phagocytic capacity. The results of the percentage of activity and phagocytic capacity of macrophage cells in the peritoneal fluid in the negative control group was 64.9% and 93.2 %, the positive control group was 66.2% and 95.0%, the 100 mg/kg BW dose group was 75.0% and 111.0%, the 500 mg/kg BW group was 82.8% and 134.6%, and the comparison group was 86.5% and 176.6%. Statistically, the percentage of activity and phagocytic capacity of mice at a dose of 100 mg/kg BW and a dose of 500 mg/kg BW were significantly different from the negative control group and the positive control group. It can be concluded that at doses of 100 mg/kg BW and 500 mg/kg BW, guava leaf ethanol extract can increase the activity and phagocytic capacity of mice.